EFFECT OF CUBAN CRUDE OIL EMULSION ON THE EFFICIENCY OF THE STEAM GENERATOR IN THERMOELECTRIC POWER PLANTS - González Díaz, Yosvany; Benítez Cortés, Isnel; García Reina, Francisco; Márquez Pañamaría, Grety; Galindo Llanes, Pablo Ángel; Prieto Montenegro, Luis Fernando (Centro Azúcar Journal, 2025)
Introduction: The use of an emulsion of Cuban crude oil in water mixed with an asphaltene dispersing agent is used to improve combustion. Its effect on steam generator efficiency needs to be studied. Objective: To evaluate the effectiveness of the water emulsion with an asphaltene dispersant additive, PentoMuls 3C, on the efficiency of the steam generator of unit 6 of the 10 de Octubre thermoelectric power plant in Nuevitas. Materials and Methods: Different concentration levels of water and asphaltene dispersant additive are used to form the emulsions. The efficiency is determined using the indirect method. Results and Discussion: In general, the parameters determined for the efficiency calculation present coefficients of variation below 10%, indicating that the emulsion does not have a significant influence at the water and additive percentage levels studied. The use of the emulsion has a direct influence on the reduction of the specific consumption of PCNM 1400 fuel, the thermal load, and an increase in the efficiency of the steam generator. With the fuel emulsion treatment and the presence of the additive, the stability of the emulsion is increased, achieving a complete and homogeneous combustion process. Conclusions: The efficiency of the steam generator increases by 0.38% with the use of emulsion, while the specific fuel consumption and thermal load of the steam generator decrease.